Safety and efficacy of Bacillus subtilis DSM 28343 for pigs for fattening. (6th June 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Bacillus   subtilis DSM 28343 when used in feed for pigs for fattening. The additive is a preparation containing viable spores of a strain of Bacillus   subtilis . This species is considered by EFSA to be suitable for the qualified presumption of safety (QPS) approach to safety assessment which requires the identity of the strain to be conclusively established, evidence that the strain is not toxigenic and that it does not show resistance to antibiotics of human and veterinary importance. The strain was found to meet the criteria for the QPS approach in the context of a previous opinion and since concerns are not expected from other components of the additive, the additive is presumed safe for all target species, consumers and the environment. In a previous opinion, the FEEDAP Panel concluded that Bacillus   subtilis DSM 28343 is not an eye/skin irritant but should be considered as a potential respiratory sensitizer and that no conclusion could be drawn on its skin sensitisation potential. These conclusions apply also to the current application. Bacillus   subtilis DSM 28343 at 2 × 10 8 CFU/kg complete feed has the potential to be efficacious in pigs for fattening.